Current management strategies for patellofemoral pain: an online survey of 99 practising UK physiotherapists - Smith, Benjamin E.; Hendrick, Paul; Bateman, Marcus; Moffatt, Fiona; Rathleff, Michael Skovdal; Selfe, James; Smith, Toby O.; Logan, Pip (BioMed Central, 2017)
Background: Patellofemoral pain (PFP) is considered one of the commonest forms of knee pain. This study aimed to identify how physiotherapists in the United Kingdom (UK) currently manage patellofemoral pain (PFP), particularly in relation to exercise prescription, and response to pain. Methods: An anonymous survey was designed with reference to previous surveys and recent systematic reviews. Practising UK physiotherapists who treat patients with PFP were invited to take part via an invitation email sent through professional networks, the ‘interactive Chartered Society of Physiotherapy (iCSP)’ message board, and social media (Twitter). Descriptive statistics were used to analyse the data. Results: A total of 99 surveys were completed. Responders reported a wide range of management strategies, including a broad selection of type and dose of exercise prescription. The five most common management strategies chosen were: closed chain strengthening exercises (98%); education and advice (96%); open chain strengthening exercises (76%); taping (70%) and stretches (65%). Physiotherapists with a special interest in treating PFP were statistically more likely to manage patients with orthotics (P=0.02) and bracing (P=0.01) compared to physiotherapists without a special interest. Approximately 55% would not prescribe an exercise if it was painful. Thirty-one percent of physiotherapists would advise patients not to continue with leisure and/or sporting activity if they experienced any pain. Conclusion: Current UK practice in the management strategies of PFP is variable. Further high quality research on which to inform physiotherapy practice is warranted for this troublesome musculoskeletal condition.